Portable paper-based electrochemiluminescence test incorporating lateral-flow immunosensors for detection of interferon-γ levels - Yuan, Shichao; Xie, Guihua; Yang, Xiang; Chen, Yu; Zhang, Hongbin (Frontiers in Bioengineering and Biotechnology, 2023)
Tuberculosis (TB) poses a serious threat to human health and social development. Accurate diagnosis of mycobacterium tuberculosis infection plays a critical role in the prevention and treatment of tuberculosis. Interferon-γ (INF-γ) release assay (IGRA) is currently the only quantitative tuberculosis infection diagnosis method. An accurate, fast, and easily handled INF-γ detection method is the key to obtaining accurate results. Herein, we report a novel paper-based electrochemiluminescence (ECL) method based on lateral flow immunosensors (LFIs) that combines the easy handling characteristics of immunochromatography and the high sensitivity of electrochemiluminescence to detect IFN-γ. To our knowledge this is the first INF-γ detection method that combines immunochromatography with electrochemiluminescence . The paper-based ECL-LFI test consists of a sample pad, conjugation pad (with binding antibody IFN-γ-Ab1 conjugated with ruthenium tripyridine), detection pad (with capture antibody IFN-γ-Ab2 immobilized on nanospheres), absorbent pad, and electrode for signal activation. The ECL signal is obtained by cyclic voltammetry scanning at a speed of 0.1 V/s in the detection area of the paper-based ECL-LFI test. In our experiments, the paper-based ECL-LFI test exhibited a minimum detection limit of 2.57 pg/mL within 12 min, and a broad detection range of 2.57–5000 pg/mL, with repeatability of 8.10% and stability of 4.97%. With the advantage of high accuracy and sensitivity, easy handling, and low user training requirements, this ECL-LFI test might be used as point-of-care testing (POCT) in the IGRA for tuberculosis diagnosis.